2016
DOI: 10.1007/s11060-016-2284-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, time trends and survival patterns of childhood pilocytic astrocytomas in Southern-Eastern Europe and SEER, US

Abstract: Pilocytic astrocytomas (PA) comprise the most common childhood central nervous system (CNS) tumor. Exploiting registry-based data from Southern and Eastern Europe (SEE) and SEER, US, we opted to examine incidence, time trends, survival and tentative outcome disparities of childhood PA by sociodemographic and clinical features. Childhood PA were retrieved from 12 SEE registries (N = 552; 1983-2014) and SEER (N = 2723; 1973-2012). Age-standardized incidence rates (ASR) were estimated and survival was examined vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
6
25
1
Order By: Relevance
“…26 Comparisons of the most recent UK findings (5-year survival [2001-2005], 82% and 71% for individuals aged 13-24 and 25-49 years, respectively) with our data are not feasible because they also included nonmalignant CNS tumors. 7 In accordance with previous studies of childhood CNS tumors 15,17 and other childhood and adult cancers, [27][28][29] rural residence was also associated with a worse prognosis; this indicates the important role of socioeconomic status and health care delivery in outcomes and that there is room for further improvements at a population level.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…26 Comparisons of the most recent UK findings (5-year survival [2001-2005], 82% and 71% for individuals aged 13-24 and 25-49 years, respectively) with our data are not feasible because they also included nonmalignant CNS tumors. 7 In accordance with previous studies of childhood CNS tumors 15,17 and other childhood and adult cancers, [27][28][29] rural residence was also associated with a worse prognosis; this indicates the important role of socioeconomic status and health care delivery in outcomes and that there is room for further improvements at a population level.…”
Section: Discussionsupporting
confidence: 85%
“…Our study also showed that male sex was independently associated with a worse prognosis, especially among older individuals and those diagnosed with astrocytomas, other gliomas, and other unspecified neoplasms. In contrast, in our previous studies of SEE data focusing on children, no sex difference in survival was identified for malignant CNS tumors; an even better prognosis for males was noted with nonmalignant childhood pilocytic astrocytoma . Several mechanisms have been implicated as contributing to the overall male vulnerability to CNS carcinogenesis .…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations